Lenders on the storm of wholesale funding shocks: Saved by the central bank? - Leo de Haan; Philip Vermeulen; Jan Willem van den End (European Central Bank (ECB), 2016)
We provide empirical evidence on banks' responses to shocks in wholesale funding, using data of 181 euro area banks over the period August 2007 to June 2013. Banks' adjustments of loan volumes and lending rates in response to funding liquidity shocks are analysed in a panel VAR framework. The results show that shocks in the securities and interbank markets have significant effects on loan rates and credit supply, particularly of banks in stressed countries. The results also suggest that central bank liquidity has mitigated this effect most clearly on lending volumes. Lending to non-financial corporations is more sensitive to wholesale funding shocks than lending to households. Moreover, bank characteristics matter for monetary transmission: loan growth of large banks that are typically more dependent on wholesale funding and of banks with large exposure to government bonds shows relatively stronger responses to wholesale funding shocks.
Keywords: G21; G32; 330; banking/financial intermediation; financial crisis